Ethics in marketing - SMITH, N. Craig; John A. Quelch (New York : McGraw-Hill, 1996)
"Ethical Marketing" examines a range of issues that marketing managers face. The book begins with a discussion of relevant ethical concepts and theories. Chapters are devoted to ethics in marketing research and target marketing, product issues, channels and pricing questions, advertising and marketing on the Internet, and selling. The volume concludes with a chapter on implementing ethical marketing through corporate policies and culture.
Includes bibliography and index
Keywords: Marketing. Business ethics